Implementasi Strategi Marketing Mix pada Pusa Street Coffee Kabupaten Pinrang dalam Menarik Minat Konsumen - Serliyana Serliyana (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
With the increasing competition in business in Indonesia, many entrepreneurs must consider the importance of marketing communication strategies in promoting their products and services. Pusa Street Coffee is a coffee shop located in Pinrang Regency, which has to compete in a highly competitive market to attract consumers through strategies and appeal that differentiate it from other coffee shops. Pusa Street Coffee implements appropriate strategies in its efforts to attract and increase the number of consumers. Therefore, Pusa Street Coffee has applied several communication strategies to promote and introduce its products to the public. This study aims to examine the implementation of the marketing mix strategies at Pusa Street Coffee in attracting consumer interest. This research uses a descriptive qualitative approach by observing existing phenomena in the field through direct observation. The study was conducted at Pusa Street Coffee in Pinrang Regency. Data collection techniques involved observations and interviews with the owners and consumers of Pusa Street Coffee in Pinrang Regency. Based on the research findings, Pusa Street Coffee in Pinrang Regency applies marketing mix strategies, including product, price, place, promotion, people, and process. This study emphasizes data in-depth analysis to achieve high-quality research results. In a Street Coffee business, the marketing mix strategy is crucial in sales to achieve sales targets.